Exploring the therapeutic mechanism of itraconazole combined with ritonavir on Candida albicans infection through network pharmacology and molecular docking - Feng, Yiyang; Feng, Wenli; Yang, Jing; Ma, Yan (Frontiers in Pharmacology, 2025)
BackgroundAutophagy induced by itraconazole and ritonavir was found involved in the pathogenesis of C. albicans. This study was designed to explore the possible molecular mechanism of itraconazole and ritonavir in the treatment of Candida albicans infection through autophagy pathway.MethodsThe overlapping targets of itraconazole and ritonavir, and those-related to C. albicans and autophagy were screened. Then the core targets were identified by protein-protein interaction (PPI) network analysis. Gene enrichment analysis of targets and the drug-target-pathway-disease network was constructed. The interactions between itraconazole, ritonavir and core targets were analyzed by molecular docking and molecular dynamics simulation. Finally, the core target-miRNA interaction network was constructed to predict candidate miRNAs.ResultsPPI network showed that PIK3R1, RELA, STAT3, HSP90AA1, TP53, JUN, GRB2, EGFR, ESR1 and TNF were potential core targets of autophagy therapy for C. albicans infection with itraconazole and ritonavir. Enrichment analysis showed that the two drugs may regulate the autophagy process through pathways including PI3K-AKT, IL-17, MAPK, Toll-like receptor, JAK-STAT and NF-κB. Molecular docking analysis indicated that itraconazole and ritonavir possess strong binding affinities with the cote target proteins, with binding free energies ranging from −5.6 to −9.5 kcal/mol. Key interactions were identified at the active sites of the targets, suggesting stable ligand-receptor complex formation. Itraconazole docked to PIK3R1 through SER-78 and GLU-82 (−9.3 kcal/mol), and ritonavir docked to PIK3R1 through ASN-85, GLU-1011 and arginine (ARG)-1088 (−7.7 kcal/mol). Molecular dynamics simulation of itraconazole and ritonavir with representative target genes lasted for 100 ns showed the structures of the formed complexes remained stable throughout. Finally, the candidate miRNAs including miR-486-5p, miR-411-5p.1 and miR-296-5p were identified.ConclusionNetwork pharmacological analysis showed a multi-target and multi-pathway molecular mechanism of itraconazole and ritonavir in the treatment of C. albicans infection, and provided a theoretical basis for subsequent studies.